2015
DOI: 10.1089/jwh.2014.4858
|View full text |Cite
|
Sign up to set email alerts
|

Do Family Responsibilities and a Clinical Versus Research Faculty Position Affect Satisfaction with Career and Work–Life Balance for Medical School Faculty?

Abstract: Background: Balancing career and family obligations poses challenges to medical school faculty and contributes to dissatisfaction and attrition from academics. We examined the relationship between family setting and responsibilities, rank, and career and work-life satisfaction for faculty in a large U.S. medical school. Methods: Baseline faculty surveys were analyzed from the first year of a 4-year National Institutes of Healthfunded study to evaluate awareness, knowledge, attitudes, and use of family friendly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 38 publications
5
42
0
Order By: Relevance
“…For example, on average, pediatric psychologists indicated tht they were only somewhat satisfied with balance of work and personal life, indicating that a major contributor to satisfaction may not be optimally met. This is consistent with the experiences reported by other healthcare professionals, suggesting there may be systemic barriers to satisfaction with work-life balance (Strong et al, 2013; Beckett et al, 2015). Pediatric psychologists may want to make efforts to limit their engagement in professional activities outside of the work setting, and colleagues may offer to support one another to limit the need to address work-related responsibilities outside of work time.…”
Section: Discussionsupporting
confidence: 90%
“…For example, on average, pediatric psychologists indicated tht they were only somewhat satisfied with balance of work and personal life, indicating that a major contributor to satisfaction may not be optimally met. This is consistent with the experiences reported by other healthcare professionals, suggesting there may be systemic barriers to satisfaction with work-life balance (Strong et al, 2013; Beckett et al, 2015). Pediatric psychologists may want to make efforts to limit their engagement in professional activities outside of the work setting, and colleagues may offer to support one another to limit the need to address work-related responsibilities outside of work time.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that female doctors tend to show more empathy (Gleichgerrcht and Decety, 2013;Cho and Jeon, 2019) and offer patients more comfort and emotional care. In addition to the increased demands of work, family responsibilities and dissatisfaction with work-life balance also play an important role in the mood of female doctors (Beckett et al, 2015). Women feel more pressure at home (Ma, 2017), leading to higher levels of EE, leading to increased depression and anxiety (Khamisa et al, 2015;Lin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…31 Beckett et al found that faculty with both child-care and clinical responsibilities were significantly more likely to report low satisfaction with work-life balance and career compared to colleagues without children and/or clinical responsibilities. 32 Villablanca et al found that flexibility policies (institutional level) were perceived as important for recruitment, retention, and career satisfaction. 33 Howell et al reported that policies were viewed as particularly important by women and younger faculty (age < 50).…”
Section: Career Flexibility and Work-life Balancementioning
confidence: 99%